Mid-Carboniferous Centralian uplift linked by U-Pb zircon chronology to the onset of Australian glaciation and glacio-eustasy - Veevers, J. J. (Australian Journal of Earth Sciences, 2009)
In 1987 C. McA. Powell and J. J. Veevers postulated that the mid-Carboniferous uplift of the Centralian fold-and-thrust belt led to the growth of an ice sheet that covered much of Australia as it drifted from low to high latitudes. They presumed that the voluminous sediment shed from the final disruption and stripping to basement of the Centralian Superbasin was transported by ice streams out of the foreland basin to the edge of the ice sheet in the eastern and west-northwestern margins. Geochronological data accrued since 1987 confirm the 330-320 Ma synchronicity of uplift and exhumation in Centralia, deposition of glacial sediment on the margins and the onset of glacio-eustasy, as indicated by cyclothemic sedimentation patterns in the Visean platform carbonates of the British Isles. These events are by-products of the 330-320 Ma merging of Gondwanaland and Laurussia in Pangaea that provided the global setting for glaciation. Probably more influential in initiating glaciation was the greater uplift in the Gamburtsev Subglacial Mountains of East Antarctica that became the focus of Permian post-glacial dispersal of sediment in East Gondwanaland.